Modernisasi Dan Tantangan Pendidikan Islam Dalam Menghadapi Perubahan Sosial Di Indonesia - Maulana Dziroshofar Putra Suliwa; Nur Khasanah (Advances In Education Journal, 2025)
Islamic education plays a crucial role in shaping personality, morals, and the direction of societal development, particularly amidst the rapid pace of modernization. In today's era of technological advancement, globalization, and social change, Islamic values ​​are often neglected due to the influence of a materialistic lifestyle and instant convenience. Islamic education serves as a source of moral and spiritual strength that can maintain a balance between worldly progress and religious values. With a learning process based on the Quran and Hadith, Islamic education not only teaches knowledge but also fosters character that is faithful, virtuous, and responsible towards the surrounding environment. By instilling values ​​such as honesty, justice, social awareness, and responsibility, Islamic education is an effective way to build a harmonious and civilized society amidst the challenges of the modern era.